A Legal Review of the PT. Asian Agri Tax Evasion Case and its Implications for the Indonesian Taxation System - Lamtiur Mariana Lely Sihombing; Armeliani Armeliani (PETITA, 2025)
Taxes are a primary source of state revenue and play a vital role in financing public needs and national development. However, non-compliance by taxpayers, such as tax avoidance and tax evasion, remains a major challenge in Indonesia’s taxation system. This study examines the tax evasion case involving PT Asian Agri Group (AAG), one of the largest in Indonesian history, to analyze corporate criminal liability and its implications for national tax policy. Using a normative juridical method with case and statute approaches, the study reveals AAG’s financial manipulation through transfer pricing, double bookkeeping, and fictitious transactions, causing a state loss of approximately IDR 1.3 trillion. The Supreme Court Decision No. 2239 K/PID.SUS/2012 imposed a fine of IDR 2.5 trillion, reinforcing the principle of corporate liability. The research reviews three corporate liability models in Indonesia, highlighting the effectiveness of holding corporations both as perpetrators and liable entities. The AAG case underscores the need for tax reform, stronger supervision, transparency, early detection technology, and taxpayer education to build a fair and accountable tax system